Governors and Prisoners: The Death of Clemency and the Making of Life Sentences without Release in Pennsylvania - Seeds, Christopher (Social justice, 2019)
The article discusses the history of the introduction of life without parole (LWOP) as a form of punishment in Pennsylvania. Also cited are the use of executive clemency to resolve sentencing injustices and regulate prison populations in the U.S., the deterioration of the relationship between governors and prisoners in the state, and the importance of commutation in the U.S. criminal justice system in the 19th and 20th centuries.